2005
DOI: 10.1128/aac.49.9.3919-3921.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Associated with Sulfadoxine-Pyrimethamine and Chlorproguanil Resistance in Plasmodium falciparum Isolates from Blantyre, Malawi

Abstract: We conducted a prevalence study of mutations in Plasmodium falciparum that are associated with antifolate resistance in Blantyre, Malawi. The dihydrofolate reductase 164-Leu mutation, which confers resistance to both pyrimethamine and chlorproguanil, was found in 4.7% of the samples. Previously unreported mutations in dihydropteroate synthase were also found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 17 publications
2
55
0
Order By: Relevance
“…Of particular interest is the study by Alker et al (1), who used real-time PCR with fluorescent probes specific for the mutation and reported a 4.7% prevalence in parasites collected from human immunodeficiency virus (HIV)-positive pregnant women in Malawi between 2001 and 2003, a finding that they validated more recently using a heteroduplex tracking assay (9). However, on biological grounds, if the quadruple-mutant alleles were present in reasonable proportions, it is hard to imagine that they would not have been selected to high levels by this time.…”
mentioning
confidence: 99%
“…Of particular interest is the study by Alker et al (1), who used real-time PCR with fluorescent probes specific for the mutation and reported a 4.7% prevalence in parasites collected from human immunodeficiency virus (HIV)-positive pregnant women in Malawi between 2001 and 2003, a finding that they validated more recently using a heteroduplex tracking assay (9). However, on biological grounds, if the quadruple-mutant alleles were present in reasonable proportions, it is hard to imagine that they would not have been selected to high levels by this time.…”
mentioning
confidence: 99%
“…However, compared to those for the published TaqManbased real-time PCR assay by Alker et al (2,3), our assay demonstrated greater sensitivity and specificity. Although the reported sensitivity of the TaqMan assay is 10 copies of the target DNA (2), this was not observed in our experiments or by another laboratory that attempted to reproduce this method (1,2,13).…”
Section: Discussionmentioning
confidence: 68%
“…In previous publications, Alker et al reported a method using hydrolysis probes (TaqMan technology) to discriminate between wild-type and mutant genotypes in the Pfdhfr gene (2,3). We compared the sensitivity and specificity of genotyping by MCA with the TaqMan methodology as described previously.…”
Section: Vol 48 2010 High-throughput Genotyping For P Falciparum Dmentioning
confidence: 99%
See 2 more Smart Citations